2021
DOI: 10.3390/j4040056
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles of Modified Pectin Targeting Galectin-3 against Severe Acute Respiratory Syndrome Coronavirus-2

Abstract: Modified pectin (MP) is a bioactive complex polysaccharide that is broken down into smaller fragments of units and used as an oral dietary supplement for cell proliferation. MP is safe and non-toxic with promising therapeutic properties with regard to targeting galectin-3 (GAL-3) toward the prevention and inhibition of viral infections through the modulation of the immune response and anti-inflammatory cytokine effects. This effect of MP as a GAL-3 antagonism, which has shown benefits in preclinical and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 114 publications
0
24
0
Order By: Relevance
“…The immunologically stimulating effects of pectin may be due to these components [57]. Pectin were created from an aqueous extract of mulberry fruits that showed immune modulatory activity by improving macrophage function [58]. Furthermore, Rubus chingii Hu pectin can be utilized as a dietary supplement for the treatment of intestinal inflammation and also has a strong inhibitory action on the mRNA level [55].…”
Section: Anti-inflammatory and Immunomodulatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The immunologically stimulating effects of pectin may be due to these components [57]. Pectin were created from an aqueous extract of mulberry fruits that showed immune modulatory activity by improving macrophage function [58]. Furthermore, Rubus chingii Hu pectin can be utilized as a dietary supplement for the treatment of intestinal inflammation and also has a strong inhibitory action on the mRNA level [55].…”
Section: Anti-inflammatory and Immunomodulatory Activitymentioning
confidence: 99%
“…Furthermore, Rubus chingii Hu pectin can be utilized as a dietary supplement for the treatment of intestinal inflammation and also has a strong inhibitory action on the mRNA level [55]. Pectin polysaccharides exhibit good anti-in flammatory activity and can be improved for the production of anti-inflammatory agents [55,58]. Further pharmaceutical applications of pectin and its modified NCs were summarized in Table 2.…”
Section: Anti-inflammatory and Immunomodulatory Activitymentioning
confidence: 99%
“…Recent studies have identified GAL-3 as a binding mediator in the attachment and entrance of viruses, including influenza A H5N1 virus, into the host cell [197,198]. This is in addition to ACE-2, which has been identified as a therapeutic target to mitigate SARS-CoV-2 entry and replication in the host cell [199]. In our previous study, the S-glycoprotein layer of probiotic L. acidophilus ATCC 4356 comprising both the amino and carboxyl-terminal domains competed with the intestinal microbiota to bind to the GAL-3 COOH terminal carbohydrate recognition domain in a colonic cancer model.…”
Section: Microbial Dysbiosis and Git-lung Stability Cross-talkmentioning
confidence: 99%
“…Uniformly 15N-labeled galectin-3 (Gal-3) was dissolved at a concentration of 20 µM in a 20 mM potassium phosphate buffer at pH 6.9, prepared with a 95% H2O/5% D2O mixture. To explore the binding of PL-M and its separate polysaccharide components (galactomannans AG and R) to Gal-3, 1 H- 15 N HSQC NMR measurements were performed. The 1H and 15N resonance assignments of recombinant human Gal-3 were reported earlier.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Even though PL-M binding-induced 15 N-Gal-3 chemical shift changes, , are relatively small, they are useful to assess the binding epitope on the lectin. This indicates that the PL-M binding epitope on Gal-3 is within the canonical sugar binding domain on the S-face of the CRD.…”
Section: Assessment Of Safetymentioning
confidence: 99%